An American friendship : Horace Kallen, Alain Locke, and the development of cultural pluralism - Weinfeld, David, 1982- (Cornell University Press, 2022)
"An American Friendship narrates the development of cultural pluralism, an idea that emerged in the early twentieth century to explain and shape American diversity, as told through the unlikely friendship of two philosophers, Jewish immigrant and Zionist leader Horace Kallen, and African American Alain Locke, intellectual godfather of the Harlem Renaissance"--